Criminal Responsibility of Paranoid Schizophrenia Patients as Murder Perpetrators to Ensure Justice - Wahyudin, Hafidz; Miranda, Yosvania; Fauzi, Yuslikha Ramandhana; Henda, Raden Henda; Rasta, Gunadi (Journal of Legal and Cultural Analytics, 2025)
This study aims to analyze criminal liability as a murder perpetrator who suffers from paranoid schizophrenia and its relation to the reasons for criminal elimination in accordance with Article 44 of the Criminal Code to ensure legal justice. The methodused in this study is normative judicalwith an approach to laws and cases from the court, after the legal materials  that have been successfully collected are then systematically  arranged and analyzed using a qualitative approach. The result of this study indicate that fraud that caused paranoid schizophrenia who commits the crime of murder can be subject to criminal sanctions or actions (double track system). In dciding such cases, the judge must prioritize the aspect of justice by concidering the opinionof a psychiatrist who observes whether the cognitive function is disturbed or not when commiting the crime of murder, if it is disturbed by characteristics such as hallucinations and delucions that cause the punishment to be unable to distinguish reality, fantasy and loss of self control , then it can be ordered in article 44 of the criminal code as a reason for forgiveness by eliminating responsibility, while if the cognitive function is not disturbed, it can beaccounted for, ther it can be accounted for criminally.